“Coming out gave me my life back:” investigating the coming out process for professional African American lesbians - Jenkins-Adams, Bertha A. (Kansas State University, 2015)
The overarching research question addressed by this qualitative dissertation is “What are the meanings, structures, and essences of the lived experiences of the coming out process for professional women who are African American lesbians (PAALs)?” The study was designed to 1) fill an existing gap in the literature by examining the coming out processes of PAALs, 2) gain an understanding of the challenges and stressors associated with the intersection of gender, race, and sexual orientation, and 3) explore the diversity of experiences that PAALs may have when coming out to family, friends, and colleagues. Purposeful sampling was used to recruit 10 women between the ages of 25 and 65. Each participant completed a face-to-face interview. Data analysis yielded 21 codes that were then aggregated into five themes and several subthemes that serve as the basis of a 5-level model for describing their coming out process: Confusion, Suppression, The Turning Point, Disclosure, and Proving Self. These levels are progressive but may overlap depending on where the individual is in the coming out process. The findings show that the experiences of PAALs demonstrated the influences of culture, race, and gender in the personal and professional lives of lesbians who have come out, or who are in the process of disclosing their sexual orientation. Additionally, some PAALs are motivated to disclose their sexual identity in order to inspire other young lesbians to come out and express their true sexual orientation.
Keywords: Homosexuality; African Americans; Lesbian; Sexuality; Stages of coming out; Professional; Individual & Family Studies (0628)